Linking Positive Psychology and Intercultural Competence by Movies: Evidence From Brunei and Romania - Popa, Daniela; Nechita, Florin; Liu, Yong; Wei Lee Chin, Shirley (Frontiers in Psychology, 2021)
Cultural consumption provides numerous benefits for individuals, especially for younger generations. Imaginary travel narratives can shape people’s perceptions about other cultures thus are useful tools for developing intercultural competences. On the other hand, positive psychology provides an approach to understand different aspects of students/youngsters’ wellbeing. This study investigates the wellbeing associated with learning the meanings of being different and growing in emotional resilience, flexibility, and openness to other cultures through movies. The positive psychology approach was used to examine the benefits of movie consumption in order to investigate the activation of five domains of wellbeing: positive emotions, engagement, relationships, meaning, and accomplishment (PERMA). The research methodology consisted of the experiment and questionnaire survey. The students’ scores on the wellbeing and intercultural competences were measured before and after the intervention. The intervention consisted of sessions of watching two example movies, Eat Pray Love and Hotel Transylvania 2, and subsequent group discussions about the movies’ respective messages. The participants’ group was formed by 236 university students from Brunei and Romania, ages between 18 and 49years old. The results showed an increase in students’ openness to other cultures and across some of the wellbeing PERMA dimensions. The study makes a theoretical contribution by connecting positive psychology and the intercultural competence constructs and the influences of movies.